The Evolution of Circulating Biomarkers for Use in Acetaminophen/Paracetamol-Induced Liver Injury in Humans: A Scoping Review - Mitchell R. McGill; Steven C. Curry (Livers, 2023)
Acetaminophen (APAP) is a widely used drug, but overdose can cause severe acute liver injury. The first reports of APAP hepatotoxicity in humans were published in 1966, shortly after the development of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) as the first biomarkers of liver injury as opposed to liver function. Thus, the field of liver injury biomarkers has evolved alongside the growth in APAP hepatotoxicity incidence. Numerous biomarkers have been proposed for use in the management of APAP overdose patients in the intervening years. Here, we comprehensively review the development of these markers from the 1960s to the present day and briefly discuss possible future directions.